Molecular Structure, Electronic and Spectral Properties Study of N, N-bis (2- Hydroxybenzalidene1, 3-Diamino-2-Propanol) Aromatic Molecule Using DFT Theory - Kafi, Dhaidan Khalaf (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, Theoretical and Experimental Properties (Molecular Structure, Electronic and Spectral Properties) of N, N-bis (2-hydroxybenzalidene1,3-diamino-2-propanol) aromatic molecule are studied. The theories used are Density Functional (DFT) with the time-dependent density functional (TDDFT). The Spectral Properties of the aromatic molecule are studied by the use of magnetic resonance spectra 1H NMR, Fourier transform-infrared (FT-IR), and Ultraviolet–visible UV/Vis spectra techniques. 1H NMR is calculated after the dissolve of the molecule in DMSO4 solution. The range of solid samples of FT-IR is from 4000 to 400 cm-1. The compound which is formed from UV/Vis spectrum is dissolved in alcohol ranged within 200-800 nm. The information of structure, basic vibration modes, change of 1H NMR isotropic chemical and ground-state UV / Visb range of the molecule are computed utilizing B3LYP/6-311G (d, p) depending on DFT. All energies for hole and electron reorganization are determined. Ultimately, the experimental data strongly agree with the measured results when compared showing. All the results implied that N, N-bis (2hydroxybenzalidene1,3-diamino-2-propanol) will be promising candidates in many applications.